The Role of Play in Children's Palliative Care - Sue Boucher; Julia Downing; Rise Shemilt (MDPI AG, 2014)
Play is the universal language of childhood and the time and opportunity to play is every child's right. The role of play as a vehicle for communication, a tool for distraction and its value in the holistic development of a normal child is without dispute. The role and value of play increase proportionately when a child is made more vulnerable through illness or disability. Despite this, providing time and opportunities to play can be overlooked or considered to be of little importance or relevance when the focus of the adult carers is the amelioration of clinical symptoms of the illness and on lessening the psychological impact the illness may have on the child. This paper outlines the role and the value of play as an integral component in the provision of palliative care for children with chronic, life-threatening and life-limiting conditions. It will show how providing appropriate equipment, sufficient time and relevant play opportunities not only improves the very sick child's psychological wellbeing, but also allows the child to cast aside the confines and restrictions imposed upon them by their illness and for a few golden moments to be nothing more than a child at play.